Cortisol and Anxiety Response to a Relaxing Intervention on Pregnant Women Awaiting Amniocentesis - Ventura, T (2012)
Background: Stress and anxiety during pregnancy have been associated with premature and low birth weight babies, presumably through fetus over exposion to glucocorticoids. Antenatal stress also seems to have long-term effects upon infant development and adult health. However, medication for stress may carry risks to the expectant mother, therefore the efficacy of nonpharmacological interventions should be investigated. Methods: Pregnant women (n = 154) awaiting amniocentesis, were randomly assigned in the morning and the afternoon to three groups for 30 min: (1) listening to relaxing music, (2) sitting and reading magazines, and (3) sitting in the waiting-room. Before and after that period, they completed the Spielberger’s State and Trait anxiety inventory and provided blood samples for cortisol. The groups were then compared regarding change in cortisol levels and anxiety. Results: Maternal cortisol and state anxiety were correlated (r = 0.25, p = 0.04) in the afternoon, but not in the morning. The larger decreases in cortisol occurred in the music group ( 61.8 nmol/L, ANOVA: p = 0.01), followed by magazine, being differences among groups more pronounced in the morning. Women in the music group also exhibited the greater decreases in state anxiety ( p < 0.001). Younger mothers with less gestational age were on average the most anxious, and also the ones with greater decreases in cortisol and anxiety levels after relaxation. Conclusion: A relaxing intervention as short as 30 min, especially listening to music, decreases plasma cortisol and self-reported state anxiety score. Pregnant women might benefit from the routine practice of relaxation in the imminence of clinical stressful events.